THE USE OF ENGLISH IN INTERNATIONAL BUSINESS COMMUNICATION (Ustozlar uchun, 2025)
English has become the dominant language of international business communication. This paper explores how English functions as a global lingua franca in corporate contexts, examines its role in facilitating cross-cultural understanding, and identifies challenges faced by non-native speakers. Data from existing research and case studies suggest that English proficiency significantly affects organizational success and global collaboration. The study concludes that strategic language policies and intercultural training are essential for effective communication in multinational environments